Feasibility Analysis of a Novel Production Method for Monolithic Integrated MEMS with Nanogaps - Hohnloser, Daniel; Schuklin, Dennis; Schmidt, Carsten; Kreitmaier, Michael; Blasini, Mario; Hagelauer, Amelie Marietta; Weigel, Robert (IEEE Sensors, 2016)
This paper analyses a novel production technique for the fabrication of microelectromechanical system (MEMS) with a gap in the scale of nanometer. The technology is based on a density-changing layer, which let a gap arise through the shrinkage of this layer. After the description of the technology, the requirements for monolithic integration and CMOS compatibility with respect to this technology are worked out. It has been discovered that there are several challenges to be overcome, especially to find a material composition which match the requirements will be important as well as to set up the process without affecting other CMOS device parameters. But if these challenges are solved the process will be suitable for various applications and enable to open up new markets.
elib2cris::1512001600,hohnloser2016
Keywords: MEMS; NEMS